2006
DOI: 10.1007/s00426-006-0090-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of visuo-spatial working memory in map learning: new findings from a map drawing paradigm

Abstract: Recently, increasing attention has been devoted to the study of the role of visuo-spatial working memory (VSWM) in environmental learning and spatial navigation. The present research was aimed at investigating the role of VSWM in map learning using a map drawing paradigm. In the first study, a dual task methodology was used. Results showed that map drawing was selectively impaired by a spatial tapping task that was executed during the map learning phase, hence supporting the hypothesis that VSWM plays an essen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
57
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 28 publications
10
57
1
2
Order By: Relevance
“…This correlation with both active and passive tasks holds especially for men, while active tasks were better predictors of women's spatial learning abilities. In addition, when an environment was learned from a map, both active and passive simultaneous working memory ability was related to survey knowledge of landmark locations and road connections (Coluccia et al, 2007). This result is not surprising, however, because a map provides simultaneous information about the layout.…”
Section: Mental Manipulation Of Spatial Informationmentioning
confidence: 87%
See 1 more Smart Citation
“…This correlation with both active and passive tasks holds especially for men, while active tasks were better predictors of women's spatial learning abilities. In addition, when an environment was learned from a map, both active and passive simultaneous working memory ability was related to survey knowledge of landmark locations and road connections (Coluccia et al, 2007). This result is not surprising, however, because a map provides simultaneous information about the layout.…”
Section: Mental Manipulation Of Spatial Informationmentioning
confidence: 87%
“…Coluccia, Bosco, and Brandimonte (2007) asked participants to perform two types of interference tasks while studying a map and then to draw a sketchmap of locations and roads. They found that tapping a spatial pattern interfered with learning both route and survey knowledge, while a verbal interference task did not affect either one.…”
Section: Encoding Spatial Textsmentioning
confidence: 99%
“…In fact, memorizing landmarks and their locations and organizing the information in a layout requires this cognitive function in the young (e.g. Coluccia et al, 2007) but there is no such evidence for the elderly. Moreover, another aspect that should be considered in interpreting the current results relates to the fact that some cognitive functions that may explain age-related differences in environment learning were not included.…”
Section: Discussion Of Results and Conclusionmentioning
confidence: 99%
“…Denis & Cocude, 1997), visuo-spatial working memory (e.g. Coluccia, Bosco, & Brandimonte, 2007) and spatial cognitive style (e.g. Nori & Giusberti, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The study by Coluccia, Bosco, and Brandimonte (2006) addresses the role of visuo-spatial working memory in various forms of map processing. Map drawing is selectively impaired by a task that taps the spatial component of visuo-spatial working memory, which suggests that this component plays an essential role in learning from maps.…”
mentioning
confidence: 99%